2010
DOI: 10.1371/journal.pone.0012963
|View full text |Cite
|
Sign up to set email alerts
|

The Plk1 Inhibitor BI 2536 Temporarily Arrests Primary Cardiac Fibroblasts in Mitosis and Generates Aneuploidy In Vitro

Abstract: BI 2536 is a new anti-mitotic drug that targets polo-like kinase 1 (Plk1) and is currently under clinical development for cancer therapy. The effect of this drug on cancer cells has been extensively investigated, but information about the effects on primary dividing cells and differentiated non-dividing cells is scarce. We have investigated the effects of this drug on primary neonatal rat cardiac fibroblasts and on differentiated cardiomyocytes and explored the possibility to use this drug to enrich differenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
42
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(48 citation statements)
references
References 33 publications
(45 reference statements)
3
42
0
1
Order By: Relevance
“…Taken together, based on the data from our studies and others, 10,15,16,19,38 we suggest that loss of functional p53 does not directly facilitates the cytotoxicity of using a FACSCalibur (BD Biosciences, Heidelberg), as described. 57 The staining of phospho-histone H3 and active caspase-3 was also evaluated by FACS.…”
Section: Methodssupporting
confidence: 66%
See 2 more Smart Citations
“…Taken together, based on the data from our studies and others, 10,15,16,19,38 we suggest that loss of functional p53 does not directly facilitates the cytotoxicity of using a FACSCalibur (BD Biosciences, Heidelberg), as described. 57 The staining of phospho-histone H3 and active caspase-3 was also evaluated by FACS.…”
Section: Methodssupporting
confidence: 66%
“…29,30 However, we and others observed that Plk1 inhibitors affect both tumor cells with functional or deficient p53 as well as primary/normal non-transformed proliferating cells. 16,19,32,38 In the previous work, based on different cancer cell lines, we have demonstrated that cancer cells with wild type p53 actually responded more sensitively to Plk1 inhibitors, as evidenced by a high degree of apoptosis induction. 15 In the present work, we have focused on the question whether mitotic stress influences the effect of Plk1 inhibitors in cancer cells in context of the p53 status.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…G2/ M arrest after PLK1 inhibition has already been shown in different cell types, including fibroblastic, primary, and cancer cells. [23][24][25] It is possible that after repeated efforts to divide, cells proceed toward death through apoptosis, which is the hallmark of PLK1 inhibition. Consistent with our findings, increased cell death rates have also been reported after PLK1 inhibition in pancreatic cancer cells, 26 hepatocellular carcinomas cells, 27 and squamous cell carcinoma cells, 28 among others.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, enhanced kinase activity associated with Plk1 and Aur-A overexpression confers a proliferative advantage in some tumors (11). Therefore, inhibitors of theses kinases are currently being evaluated for therapeutic use (11)(12)(13)(14)(15)(16). However, the feasibility of using these kinases as anticancer drug targets is a matter of controversy.…”
Section: Introductionmentioning
confidence: 99%